“I Feel Like I’m Going to Win”: Superstition in Gambling - D’Agati, Marina (Qualitative Sociology Review, 2014)
Drawing on in-depth interviews with recreational gamblers (N=67), the paper focuses on superstitious beliefs and practices used by players of various games to influence or control outcomes. The study was conducted in the spirit of the interpretative approach formed by folklorist Alain Dundes (1961). Results suggested that superstition, in a variety of forms – signs, magic, conversion – was clearly an accepted part of gambling for most respondents. Although more pronounced in games of chance, superstition appeared to be more significant in the experience of interviewees who played skill games, creating “illusion of control.” Future research on the link between superstition and religion, and on the role of social networks in fostering and developing superstition-related knowledge is warranted.